2022
DOI: 10.3390/polym14081571
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Dimensional Stability of Poplar Wood Modified by Pre-Compression and Post-Vacuum-Thermo Treatments

Abstract: Fast-growing poplar wood has the bottleneck problems of inferior mechanical strength and poor dimensional stability. In this study, the wood was modified by combined treatments of pre-compression and post-vacuum-thermo modification to improve its mechanical strength and dimensional stability, simultaneously; in addition, the variation law of mechanical properties of the wood with compression ratio as well as the improvement effect of dimensional stability of the treated wood were mainly studied. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…In the study [14], wood was modified by a combined pre-compression treatment and post-vacuum thermal modification to simultaneously improve its mechanical strength and dimensional stability. The law of changes in the mechanical properties of wood with the degree of compression was investigated, as well as the effect of improving the dimensional stability of wood treated in this way.…”
Section: Horbachova Et Almentioning
confidence: 99%
“…In the study [14], wood was modified by a combined pre-compression treatment and post-vacuum thermal modification to simultaneously improve its mechanical strength and dimensional stability. The law of changes in the mechanical properties of wood with the degree of compression was investigated, as well as the effect of improving the dimensional stability of wood treated in this way.…”
Section: Horbachova Et Almentioning
confidence: 99%
“…The wood obtained by using a 70% compression ratio and heat treatment at 190 °C showed 26% higher dimensional stability than compressed wood alone. 7 Compared with physical methods, chemical modification 10−12 is a more permanent and effective strategy to improve dimensional stability. On the one hand, the amount of hydroxyl groups in the wood cell wall would be reduced by graft modification.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, cell wall modification is the critical factor in improving wood dimensional stability. Generally, physical methods are preferred in industry due to cost advantage. In physical modification, heat treatment and wax impregnation are reported to reduce the maximum swelling of the wood by 31 and 29%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, densified wood can replace hardwood as well as other precious wood species. After compression densification treatment, the wood undergoes significant changes in organization at the cellular level and in overall physical and mechanical properties [39][40][41][42]. Results have shown that the strength and toughness of compressed wood pretreated by delignification are considerably higher than those of natural wood [43], and the specific strength is even superior to that of some metals and alloys [44,45].…”
Section: Introductionmentioning
confidence: 99%